2009
DOI: 10.1007/s10562-009-0136-3
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of Cellulose into Sorbitol over Carbon Nanotube-Supported Ruthenium Catalyst

Abstract: Cellulose samples with different crystallinities (33-85%) were prepared by treating a commercial cellulose (crystalline, 85%) with phosphoric acid under different conditions. Supported Fe, Co, Ni, Pd, Pt, Rh, Ru, Ir, Ag, and Au catalysts were examined for the conversion of cellulose with a crystallinity of 33% in water medium in the presence of hydrogen, and Ru was found to be the most effective catalyst for the formation of sorbitol. We demonstrated that carbon nanotubes (CNTs) were the most efficient support… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
152
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 291 publications
(158 citation statements)
references
References 38 publications
(48 reference statements)
5
152
1
Order By: Relevance
“…For example, Pt/g-Al 2 O 3 catalyzed the conversion of cellulose to yield 25 % and 6 % of sorbitol and mannitol, respectively. Alternatively, on a Ru/C catalyst Luo et al reported yields of 30 % and 10 % of sorbitol and mannitol, respectively.[3] Most notably, in such studies less-expensive Ni catalysts consistently exhibit inferior performances towards sugar alcohol production (Supporting Information, Table S1), [2,[4][5] in agreement with their known unselective hydrogenolysis behavior. [8] The main difficulty in using conventional heterogeneous catalysts for bulky cellulose substrates is the limited accessibility of the active catalytic sites.…”
mentioning
confidence: 87%
See 1 more Smart Citation
“…For example, Pt/g-Al 2 O 3 catalyzed the conversion of cellulose to yield 25 % and 6 % of sorbitol and mannitol, respectively. Alternatively, on a Ru/C catalyst Luo et al reported yields of 30 % and 10 % of sorbitol and mannitol, respectively.[3] Most notably, in such studies less-expensive Ni catalysts consistently exhibit inferior performances towards sugar alcohol production (Supporting Information, Table S1), [2,[4][5] in agreement with their known unselective hydrogenolysis behavior. [8] The main difficulty in using conventional heterogeneous catalysts for bulky cellulose substrates is the limited accessibility of the active catalytic sites.…”
mentioning
confidence: 87%
“…[2][3][4][5] The principal reason is that these polymeric biomolecules with a semicrystalline structure cannot penetrate the pores of conventional heterogeneous catalysts. Advances in the conversion of cellulose therefore require the design of efficient multifunctional catalysts with sterically accessible sites.…”
mentioning
confidence: 99%
“…So, the suitable catalyst should provide acid sites for the hydrolysis and metallic sites for the hydrogenation. Ruthenium (Ru) catalysts have shown to be the most effective in the direct conversion of cellulose into polyols [2,11,12]. However, the problem about the optimization of the support remains.…”
Section: Introductionmentioning
confidence: 99%
“…However, the problem about the optimization of the support remains. Activated carbon (AC) is most often used to stabilize Ru particles and is cheap [13], whereas carbon nanotubes [11,14] and nanofibers [15] are promising supports, but are more expensive.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation